How do dual-employed couple parents manage without childcare? Can it be explained by fathers' involvement in childcare? - Baxter, Jennifer; Gray, M (My University, 2010)
Employment decisions of parents with young children are inextricably linked with the question about who will care for their children. In couple families, one solution to the childcare question, adopted by a substantial minority of dual-employed families, is to organise their work in such a way that they do not need to use any non-parental care. This paper seeks to determine to what extent, and in what circumstances, this is made possible through a greater sharing of childcare between parents. This paper uses data on dual-employed families from the infant cohort of the Longitudinal Study of Australian Children (LSAC), as at 2004 and 2006, to examine the use of non-parental childcare and fathers' involvement in childcare in these families. At the first wave, the children are aged 3 to 14 months old and at the second wave these same children are aged 28 to 40 months. We focus just on these two sources of data since most of these children are not yet old enough to attend early education. (At older ages a very large proportion of children spend some time in childcare or preschool, regardless of their parents' employment status.) Our findings suggest that is incorrect to assume this use of parental care only is largely facilitated by the involvement of fathers. While this is true in some families, in many it is instead about the use of part-time work or self-employment of mothers, which appears to allow employment to be worked around or alongside children's care needs.
Keywords: Families; Families -- Fathers; Families and relationships; Families; Fathers; Families and relationships